2021
DOI: 10.1007/s00265-021-03055-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of social structure and dynamics in the maintenance of endemic disease

Abstract: Social interactions are required for the direct transmission of infectious diseases. Consequently, the social network structure of populations plays a key role in shaping infectious disease dynamics. A huge research effort has examined how specific social network structures make populations more (or less) vulnerable to damaging epidemics. However, it can be just as important to understand how social networks can contribute to endemic disease dynamics, in which pathogens are maintained at stable levels for prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 158 publications
0
16
0
Order By: Relevance
“…A long‐recognised cost of being social is the increased risk of encountering a socially transmitted infectious disease or parasite. Studies analysing disease transmission through social networks confirm that high sociability can increase transmission by increasing the frequency of interactions with other individuals, but that the specific dynamics of transmission may differ among diseases and ecological settings (Silk & Fefferman, 2021; Albery et al ., 2021a). Indeed, such studies have demonstrated that the transmission of contagious diseases appears to be related to network architecture (Kappeler, Cremer & Nunn, 2015; Silk et al ., 2019).…”
Section: The Maintenance Of Variation In Sociability and Its Costs An...mentioning
confidence: 99%
“…A long‐recognised cost of being social is the increased risk of encountering a socially transmitted infectious disease or parasite. Studies analysing disease transmission through social networks confirm that high sociability can increase transmission by increasing the frequency of interactions with other individuals, but that the specific dynamics of transmission may differ among diseases and ecological settings (Silk & Fefferman, 2021; Albery et al ., 2021a). Indeed, such studies have demonstrated that the transmission of contagious diseases appears to be related to network architecture (Kappeler, Cremer & Nunn, 2015; Silk et al ., 2019).…”
Section: The Maintenance Of Variation In Sociability and Its Costs An...mentioning
confidence: 99%
“…These include, but are not limited to, social context, sampling biases and demographic and environmental stochasticity. Population social structure, for example, will constrain pathogen spread within a host population (Silk & Fefferman, 2021) and contact patterns will provide potential transmission routes through different parts of the host population network (Sah et al, 2017). Similarly to the spatial example above, failing to account for social context can lead to biased estimates of maintenance potential if there are asymmetries in contact rates or shedding between individuals in different regions of the network (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the fundamental reproductive number R0—the number of infected individuals produced by an average susceptible individual in a fully susceptible population—is the product of a dynamic disease process and is the canonical, although not exclusive (e.g. critical community size, long‐term transient persistence; Silk & Fefferman, 2021; Viana et al, 2014), metric of maintenance potential (Fenton et al, 2015; Palmer, 2013; Stewart Merrill & Johnson, 2020). When R0>1 for a particular species in a multihost community, this means that a pathogen can invade and, given fairly general assumptions about host births and deaths (Fenton et al, 2015), persist enzootically.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, correlative evidence across primate species suggests bidirectional effects between host social structure and their pathogens. Silk and Fefferman (2021) examine the role of social structure and social dynamics in maintaining endemic disease. Through their synthetic theoretical and empirical work, they highlight the importance of both social structure and dynamics in maintaining reservoirs of agricultural and zoonotic diseases.…”
Section: Sociality and Disease: Behavioral Perspectives In Ecological...mentioning
confidence: 99%